ISBAT NIKAH SUDUT PANDANG UNDANG-UNDANG PERKAWINAN (Faculty of Law, University of Palembang, 2023)
Marriage Isbat is an application for marriage validation that is submitted to the Religious Court to declare the marriage valid and has legal force. Marriage certificate is the determination of the marriage of a man with a woman as husband and wife which has been carried out in accordance with the provisions of the Islamic religion, that is, the conditions and pillars of marriage have been fulfilled. However, this previous marriage has not been or has not been registered with the competent authority. Through marriage certificates, marriage becomes legal according to their religion, legal certainty, so that the legal consequence of having a marriage registration is that marriages are considered valid, both according to their respective religions and beliefs, and legal according to the law because they have been recorded at the Office of Religious Affairs (KUA) or the Registry Office. Civil. The status of the child born in the marriage has a good civil relationship with the mother and father, giving rise to inheritance rights for the child and his parents (father).